Perbandingan Implementasi P5 di SMA Kota Bandung - ., Allyah Azizah Lyana; ., Amelia Najwa Ramdhani; ., Destia Septiani; ., Juliana Ayu Santoso; ., Sabrina Fatihah Purnama (CV. ITTC INDONESIA, 2023)
This study aims to analyze the comparison of the implementation of the Pancasila Student Profile Strengthening Project or P5 as an application of independent curriculum program learning in several Bandung High Schools. The method used is a comparative descriptive method, which analyzes the comparison of each school that has been observed. The data collection techniques used are observation, interview with the vice principal of the curriculum and the P5 program team in each school observed. At this time, the education system in Indonesia has undergone many changes due to the Covid-19 pandemic, so the government needs to strive to restore the educational situation during the Covid-19 pandemic in order to improve the quality of education. In implementing the independent curriculum, students are required to have freedom in determining learning materials, so this curriculum was developed as a more flexible curriculum that focuses on developing the character and competence of students, so that students play an active role in implementing P5 activities in the independent curriculum program. In this study, there are several aspects used in the implementation of the independent curriculum program, namely independent curriculum planning, independent curriculum implementation, and independent curriculum evaluation.